Warung Angkringan Bertahan di Tengah Jaman: Membangun Kepuasan Melalui Kualitas Layanan - Widyadmono, V Mardi; Endang Wijayanti, Lilis (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2023)
Angkringan is a typical business in many regions of Indonesia. This business is business that is very easy to duplicate by other business people. It is not too surprising that the angkringan business is mushrooming everywhere. The reality that not all angkringan last long is the reality that prompted this research to emerge. What makes the angkringan business survive and others do not? Using quality of service as a perspective to see that difference in relation to customer satisfaction. With 225 respondents using angkringan in Yogyakarta. The survey was conducted by distributing questionnaires to respondents on an accidental basis. The findings show that angkringan stalls can survive by paying attention to service quality, especially in the dimensions of Tangible, Reliability, Assurance, and Empathy. While the Responsiveness dimension is not proven to affect consumer satisfaction. This research has implications for angkringan stall managers in terms of efforts and strategies to increase consumer satisfaction.